Amplification of regulatory T Cells using a CD28 superagonist reduces brain damage after ischemic stroke in mice - Na, Shin-Young; Mracskó, Eva; Liesz, Arthur; Veltkamp, Roland (Stroke, 2015)
Background and Purpose—Neuroinflammation plays an important role in ischemic brain injury. Regulatory T cells (Treg) are important endogenous immune modulators. We tested the hypothesis that Treg a...
Orginally published 6 Nov 2014
Gesehen am 10.08.2020